Peningkatan Keterampilan Bercerita Melalui Kartu Gambar pada Mahasiswa Program Studi Pendidikan Anak Usia Dini di IAIS Sambas - Saripah Saripah; Siti Misra Susanti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Storytelling is one of the habits of ancient people in conveying a message or telling an activity that has happened. A person's storytelling skills are closely related to the speaking skills that the person has. There are two important elements that must be mastered by students in storytelling, namely linguistics and the elements of what is told. Accuracy of speech, grammar, vocabulary, fluency and smoothness, illustrate that students have good speaking skills. Departing from the phenomena in the field, researchers see that students' storytelling skills are still lacking. This study aims to explore the improvement of storytelling skills in students of early childhood education study programs using picture cards. The method used is a quantitative approach with a descriptive type of research. The results show a significant increase in storytelling skills using picture cards.